Logistics and Information Technology: A Systematic Literature Review of Nanostores from 2014 to 2023 (LACCEI, 2024)
The purpose of this study is to conduct a systematic literature review (SLR) using bibliometric tools to understand both existing knowledge base and trends of research about nanostores in logistics and supply chain management (SCM). Such knowledge and trends will help to identify emerging research topics on the subject. More than 430 publications, selected through a keyword combination search from top-level databases of peer-reviewed academic publishers from period 2014-2023 are analysed for the purposes of this study, which presents an assessment to determine authors, academic publishers, years, and countries, among other key aspects. These allow identifying research and emerging research topics. A content analysis of the relevant publications within specialized literature of nanostores is presented. The findings make unique contributions by using bibliometric analysis to explore the status of research on nanostores, logistics and SCM, identifying existing topics from three dimensions out of six categories of paper content, discussing current shortcomings, challenges, and the potential areas of future research. This paper provides a comprehensive view of the range of topics of importance that have been discussed in the literature of nanostore, logistics and SCM. These research trends can serve as a basis for owners, researchers, and practitioners to improve decision making and develop strategies. The paper employs SLR in a publication to review the nanostore retail literature for the first time (i.e., important methodological contribution to the field of logistics, SCM and nanostores studies, where there is no SLR), to understand and reorganize available knowledge from such a dynamic and developing field, with heterogeneous studies, and concepts that often poorly operationalized, thus not providing sufficient assistance to owners, researchers, and practitioners, in their efforts to implement logistics and SCM practices in nanostores.